The complete chloroplast genome sequence of Taiwania flousiana - Wang, Qinghua (Mitochondrial DNA B Resour, 2020)
The first complete chloroplast genome (cpDNA) sequence of Taiwania flousiana was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 132,565 bp in length, contains a large single copy region (LSC) of 72,930 bp and a small single copy region (SSC) of 59,477 bp, which were separated by a pair of inverted repeats (IR) regions of 79 bp. The genome contains 121 genes, including 83 protein-coding genes, 4 ribosomal RNA genes, and 34 transfer RNA genes. Further phylogenomic analysis showed that T. flousiana and Taiwania cryptomerioides clustered in a clade in Cupressaceae family.